Active Antenna Tracking System with Directional Antennas for Enhancing Wireless Communication Capabilities of a Networked Robotic System. Issue 3 (6th May 2015) - Min, Byung‐Cheol; Matson, Eric T.; Jung, Jin‐Woo
Abstract : This paper presents a networked robotic system design capable of enhancing wireless communication capabilities (communication range and bandwidth). The core of the system is active antenna tracking with directional antennas. The proposed system is decentralized and consists mainly of a mobile robot system and a command center system. Each system is equipped with off‐the‐shelf network devices such as antennas, access points (AP), and network switches. For directional antennas to be beneficial to our system, we propose a weighted centroid algorithm (WCA) to provide active antenna tracking and direction‐of‐arrival (DOA) estimation. This system can be used in GPS‐denied environments as our system does not require the aid of additional sensors to provide location information. Through extensive field experiments in different environments, including a fire training center and with various antenna selections, such as omni‐to‐omni, omni‐to‐directional, and directional‐to‐directional antennas, we demonstrate the effectiveness of our proposed system. We expect that our system can be applied in a variety of rescue, surveillance, and emergency scenarios where high bandwidth and long‐distance communications are needed.